RANCANG BANGUN MODUL TRAINER KIT SISTEM KENDALI BERBASIS DIGITAL - Indra Christian, Febry; Rahardjo, Pratolo; Alit Swamardika, Ida Bagus; Divayana, Yoga; Oka Saputra, Komang; Elba Duta Nugraha, I Putu (Jurnal SPEKTRUM; Vol 11 No 2 (2024): Jurnal SPEKTRUMDO - 10.24843/SPEKTRUM.2024.v11.i02.p15, 2024)
A control system is defined as a combination of several components that aim to produce a system response in accordance with the desired process variables. Therefore, control systems are now widely used in various fields such as industry, automotive, public facilities, and household appliances. Especially in the industrial field, control systems play a role in improving production quality and reducing production costs. To create qualified human resources who have a good understanding in this field, universities have an important role in realizing this. One of them is Udayana University through the Electrical Engineering Study Program in the Independent Learning Curriculum in the Control System + Lab Course. This study aims to design a Digital-Based Control System + Lab Trainer Kit Module using Arduio Uno to support the process of implementing practicum in the laboratory. In the trainer kit module, there will be three systems designed, which are DC motor direction and speed control system using L298N motor driver, water heater control system using DS18B20 temperature sensor, and also water level control system using HC-SR04 ultrasonic sensor.